Republic of San Marino : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation highlights that rising unemployment, stagnant wage growth, and lower confidence have all contributed to falling private consumption and low inflation in San Marino. Financial sector balance sheets have continued to compress on the back of steady outflows of deposits. Directors have welcomed the measures taken to contain the 2012 budget deficit but called for a comprehensive medium-term consolidation plan, given growing fiscal risks. Directors have also stressed the need for a deficit-financing plan, which could involve issuing debt instruments on capital markets.